Nanocellulose and Nanocarbons Based Hybrid Materials Synthesis, Characterization and Applications - Trache, Djalal; Thakur, Vijay Kumar (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This highly informative and carefully presented book discusses the preparation, processing, characterization and applications of different types of hybrid nanomaterials based on nanocellulose and/or nanocarbons. It gives an overview of recent advances of outstanding classes of hybrid materials applied in the fields of physics, chemistry, biology, medicine, and materials science, among others. The content of this book is relevant to researchers in academia and industry professionals working on the development of advanced hybrid nanomaterials and their applications.